The importance of an evolutionary perspective in conservation policy planning. Issue 24 (December 2013) - Moritz, Craig C.; Potter, Sally
<x xml:space="preserve">Abstract</x> Prioritization of taxa for conservation must rest on a foundation of correctly identified species boundaries, enhanced by an understanding of evolutionary history and phylogenetic relationships. Therefore, we can incorporate both evolutionary and ecological processes into efforts to sustain biodiversity. In this issue of Molecular Ecology, Malaney & Cook (2013) highlight the critical value of an evolutionary biogeographical approach, combining multilocus phylogeography with climatic niche modelling to infer phylogenetically weighted conservation priorities for evolutionary lineages of jumping mice across North America. Remarkably, they find that the Preble's meadow jumping mouse (Zapus hudsonius preblei), long debated as a threatened taxon, in fact represents the southern terminus of a relatively uniform lineage that expanded well into Alaska during the Holocene. By contrast, some other relictual and phylogenetically divergent taxa of jumping mice likely warrant greater conservation priority. This study highlights the value of integrative approaches that place current taxonomy in a broader evolutionary context to identify taxa for conservation assessment, but also highlights the challenges in maintaining potential for adaptive responses to environmental change.